The Influence of Attractiveness, Credibility and Brand Attitudes towards Consumer Buying Intentions on Skincare Products - Regina Regina; Rina Anindita (Universitas Bumigora, 2022)
This research aims to find out the influence of attractiveness, credibility, brand attitudes on consumer buying intentions. This study is a quantitative study using primary data in the form of questionnaires. The sample in this study was women aged 20 to >51 years and domiciled in Tangerang Regency. The sample was selected using purposive sampling techniques. The data is analyzed using the Structural Equation Model (SEM). The results of this study show that good attractiveness does not improve brand attitude, but good attractiveness will increase consumers' buying intentions. Good credibility will improve the brand's attitude, but good credibility does not increase a consumer's buying intentions. Then, a good brand attitude can increase a consumer's buying intentions.